Shariah Market Based On Social Media; A Strategic Conflict For Improving Sale - Eka Anggraini Aritonang; Sri Mauliza (Proceeding International Seminar of Islamic Studies, 2019)
: The emergence of instantaneous products has a major impact on people's perspectives and behavior. Many people do not want to be difficult in owning a house, so many companies use this great opportunity to build a medium business engaged in developers. The business undertaken began with the use of own capital, which has now expanded to larger businesses aimed at supporting the government's